ANALISA TENTANG ABORTUS PROVOKATUS DALAM ILMU PENGETAHUAN KEDOKTERAN DI TINJAU DARI HUKUM PIDANA - Syahrani Syahrani (Universitas 17 Agustus 1945 Samarinda, 2014)
Abstract Advances in medical science and technology development is extremely important role in the enforcement of criminal law. Provokatus abortion or abortion provokatus medisinalis criminalist is not a group of young people, but also the elderly who already have many children and little children. Maaih parents in childbearing but tidk desired pregnancy due to economic factors, health and so on. In order to maintain the authority and legal certainty, it should provokatus abortion or abortion based on medical indication, immediately in the form of a law that is legal, to avoid the vagueness of the law that govern them. In criminal law legislation regarding abortion provokatus for the benefit of health or medisinalis.